Temperature and Water Quality-Related Patterns in Sediment-Associated Symbiodinium Communities Impact Symbiont Uptake and Fitness of Juveniles in the Genus Acropora - Quigley, Kate M.; Bay, Line K.; Willis, Bette L. (Frontiers in Marine Science, 2017)
The majority of corals acquire their photo-endosymbiont Symbiodinium from environmental sources anew each generation. Despite the critical role that environmental availability of Symbiodinium plays in the potential for corals to acclimate and adapt to changing environments, little is known about the diversity of free-living Symbiodinium communities and how variation in these communities influences uptake and in hospite communities in juvenile corals. Here we characterize Symbiodinium community diversity in sediment samples collected from eight reefs representing latitudinal and cross-shelf variation in water quality and temperature regimes. Sediment-associated Symbiodinium communities were then compared to in hospite communities acquired by A. tenuis and A. millepora juveniles following 11 – 145 days of experimental exposure to sediments from each of the reefs. Communities associated with juveniles and sediments differed substantially, with sediments harbouring four times more unique OTUs than juveniles (1125 OTUs vs. 271). Moreover, only 10.6% of these OTUs were shared between juveniles and sediments, indicating selective uptake by acroporid juveniles. The diversity and abundance of Symbiodinium types differed among sediment samples from different temperature and water quality environments. Symbiodinium communities acquired by juveniles also differed among the sediment treatments, despite juveniles having similar parentage. Moreover, Symbiodinium communities displayed different rates of infection, mortality, and photochemical efficiencies, important traits for coral fitness. This study demonstrates that the biogeography of free-living Symbiodinium types found within sediment reservoirs follows patterns along latitudinal and water quality environmental gradients on the Great Barrier Reef. We also demonstrate a bipartite strategy for Symbiodinium uptake by juvenile corals of two horizontally-transmitting acroporid species, whereby uptake is selective within the constraints of environmental availability.